Green coating and consolidants ease the restoration of historical objects. (Research'eu results magazine)
Restoring cultural heritage objects is difficult enough, at the same time having to maintain their authenticity, but it becomes even more of a brainteaser when adding environmental concerns to the mix. New materials developed and tested under the HEROMAT project will help restorers to take on both challenges simultaneously.